A description and evaluation of the physical and financial characteristics of dairy farms operating on soil types classified as poorly drained and associated with high rainfall. (24th January 2019) - Hanrahan, Liam; Tuohy, Pat; McHugh, Noirin; O'Loughlin, James; Moran, Brian; Dillon, Pat; Breen, James; Wallace, Michael; Shalloo, Laurence
Abstract: The physical and financial performance data used for analysis were obtained over a 6‐year period (2010–2015), from two different databases including a nationally representative data set of dairy farmers and a detailed data set of seven individual farms. Initial analysis indicated significant variations across soil type and region, across a wide range of physical and financial parameters. Further detailed analysis was completed using a group of seven farms participating in a Heavy Soils Programme (HSP), which were compared to different cohorts of the nationally representative database (National Farm Survey [NFS]), ranked on net profit per ha. The HSP farms utilized larger quantities of grass DM per ha per year than the median of the NFS farms, at similar grazing season lengths, but were using lower levels of purchased feed. Economic analysis indicated the HSP farmers achieved significantly lower net profits per hectare to the NFS median group but significantly higher net profits per kg of fat and protein. The HSP farms also achieved significantly greater overall net farm income per year (€83, 788), when compared to the median nationally (€67, 898), over the 6‐year period (excluding owned land and labour). The mean return on assets ascertained by the HSP farmers was also significantly greater, at 5.75% per year compared to 3.49% achieved by the median of NFS farms. In conclusion, this study has indicated that efficient dairy businesses operating on poorly drained soils can be as profitable as those across all ranges of soil types.